Scottish romanticism and collective memory in the British Atlantic - McNeil, Kenneth (Edinburgh critical studies in romanticism., 2020)
This book provides an in-depth examination of Scottish Romantic literary ideas on memory and their influence among various cultures in the British Atlantic.